2016
DOI: 10.5812/jjm.40543
|View full text |Cite
|
Sign up to set email alerts
|

Growing Incidence of Non-Dermatophyte Onychomycosis in Tehran, Iran

Abstract: BackgroundNon-dermatophyte onychomycosis (NDO) is caused by a wide range of mold fungi other than dermatophytes, and has been reported at various rates in different countries worldwide. Studies on the incidence of NDO in the community are essential for understanding its epidemiology and control, as well as for the appropriate treatment of these infections.ObjectivesIn this study, the incidence of NDO in Tehran, Iran, was compared to the incidence of onychomycoses due to dermatophytes and yeasts.MethodsFrom 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Review of the literature and the data from this study point out that contrary to the popular belief emphasizing on the dermatophytes as the leading causes of onychomycosis worldwide, it is at least from one decade ago that yeasts (alone or in combination with NDMs) are the main agents of onychomycosis in most areas of Iran [ 11 , 12 - 14 , 30 ], and even other parts of the world [ 5 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 56%
“…Review of the literature and the data from this study point out that contrary to the popular belief emphasizing on the dermatophytes as the leading causes of onychomycosis worldwide, it is at least from one decade ago that yeasts (alone or in combination with NDMs) are the main agents of onychomycosis in most areas of Iran [ 11 , 12 - 14 , 30 ], and even other parts of the world [ 5 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 56%
“…A 2015 study showed non-dermatophyte moulds emerging as a leading cause of onychomycosis in south-east Rajasthan in India [ 4 ]. In 2016, a growing incidence of non-dermatophyte onychomycosis was reported from Tehran, Iran with Aspergillus as the most common cause, followed by Fusarium [ 5 ]. NDF have also been seen to colonize damaged nail plates [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among NDMs the isolation rates of various species vary Fusarium spp (31%) is in accordance to recent case reports and epidemiological studies. 5,[26][27][28][29][30] Although study is not a comprehensive epidemiological survey this study demonstrated that 29.3% of onychomycosis cases are due to NDMs, which is 3 times more than the isolation found in the last study conducted in Bangalore, India. 12 The fact that non-dermatophyte moulds is the most common pathogen implicated for onychomycosis in this population, poses a challenge as its response to oral antifungal is unpredictable.…”
Section: Discussionmentioning
confidence: 96%
“…Similar pattern of isolation was noted in recent studies. 5,6,17,18 The presence of superficial fungal infection was seen among seven patients, majority of whom had tinea pedis. T. rubrum was most commonly isolated in this group, which is in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation